Fuel Flexible Sofc with a Mo-Doped Ceo2/Ysz Mesoporous Anode Fabricated by the Evaporation Induced Self-Assembly (Eisa) Method - Zagal-Moya, J; Zagal-Moya, J; Donoso-Garcia, P; Tasca-Gottardo, F; Tasca-Gottardo, F; Fuentes-Pereira, I (Elsevier B.V., 2024)
The design and extension of the triple phase boundary (TPB) in fuel cell electrodes play a key role in electric power generation, TPB enhancement can be achieved by direct growth of mesoporous anode structures on the electrolyte of a SOFC. In this study, we present a novel approach to enhance the performance of solid oxide fuel cells (SOFCs) by designing and extending the TPB through direct growth of mesoporous anode structures on the electrolyte. Mesoporous Mo-doped CeO2/YSZ anodes were successfully grown directly on a commercial YSZ substrate via the EISA method. These anodes exhibited remarkable stability over 60 h of testing when fueled with H2 or syngas, highlighting their fuel-flexibility. Our results show that these SOFCs achieved their highest power densities when fueled with H2, achieving a remarkable 135 % increase in electrical power density compared to previously reported values for the same anode material without microstructure control. Moreover, compared to SOFCs with mesoporous nanoparticles-based anodes, the EISA approach resulted in a 74 % higher electrical power density. Although this method improves the performance of the SOFC, there is evidence of an increase in its polarization resistance attributed to mass transport limitations through the mesoporous structure. © 2024 The Authors